A Financial Analysis of Ludhiana's Migrant Labour. (March 2017) - Mehra, Shruti
This study focuses overall on the financial health of industrial migrant labour working in the industrial units of Ludhiana city in terms of their income, consumption, expenditure, savings and remittance. Our survey reveals that the average annual income of these labourers was ₹35, 112 while their average annual saving was ₹7, 548 and their average annual remittance was ₹5, 786. About two-thirds of the total industrial migrant labour surveyed remitted their entire savings. The meagre amount of their savings highlights the plight of this labour and their families back home. Indebtedness was identified as the most common reason for the remittance of money. But compared to their local counterparts, it seems that migrants experienced an improvement in their standards of living after they migrated.